Kontuzje i urazy w wioślarstwie =Injuries and trauma in rowing - Aleksandra Kopeć; Marek Napierała; Walery Zukow (Kazimierz Wielki University, 2016)
Kopeć Aleksandra, Napierała Marek, Zukow Walery. Kontuzje i urazy w wioślarstwie =Injuries and trauma in rowing. Journal of Education, Health and Sport. 2016;6(4):331-354. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50353 http://ojs.ukw.edu.pl/index.php/johs/article/view/3484   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.     KONTUZJE I URAZY W WIOŚLARSTWIE Injuries and trauma in rowing Aleksandra Kopeć, Marek Napierała, Walery Zukow   Uniwersytet Kazimierza Wielkiego w Bydgoszczy     Słowa kluczowe: urazy, kontuzje, wioślarstwo, rehabilitacja   Key words: injuries, rowing, rehabilitation     Streszczenie                                                Celem badań było określenie urazów i kontuzji w wioślarstwie. Przeprowadzone badanie miało na celu wskazanie jak wielu wioślarzy cierpi z powodu kontuzji i urazów doznanych podczas obciążających treningów.  W badaniu wzięli udział wioślarze nadal trenujący oraz ci, którzy zakończyli karierę. Do tego celu zostało wykorzystane badanie sondażowe.                                                Wyniki badań, wykazały że kontuzje i urazy bardzo często towarzyszą wioślarzom. Dyskopatia to najczęstsza dolegliwość wśród zawodników, zarówno młodych jak i tych starszych. Niepokojący jest fakt, że bardzo duża część sportowców, nie wspomaga leczenia swoich urazów dostępnymi zabiegami. Rzadko też korzystają z rehabilitacji. Większość z badanych po przebytej kontuzji wraca do dalszego uprawiania sportu. Wioślarze                martwią   się           o              swoje       zdrowie i o to, jak będą funkcjonować po zakończeniu kariery wioślarskiej.     Abstract The aim of the study was to determine the injury and injury in rowing. Our audit was to identify as many rowers suffer from injuries and trauma suffered during training aggravating. The study was attended by paddlers still trainees and those who have completed a career. For this purpose it has been used survey. The test results showed that injuries and injuries often accompany the rowers. Discopathy is the most common ailment among players both young and older ones. The alarming fact is that a very large part of the athletes, does not support the treatment of their injuries available treatments. Rarely also benefit from rehabilitation. Rowers are worried about their health and about how they will function after the rowing career.